2002
DOI: 10.4102/sajp.v58i2.236
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity in pulmonary Tuberculosis

Abstract: Aims: To determine the exercise capacity of patients suffering from pulmonary tuberculosis infection and then compare thisvalue to the normal. To determine if the regression equation for TB is comparable to that of patients with chronic obstructive pulmonary disease(COPD). To provide guidelines for clinical practice of physiotherapyshould exercise capacity be found to be reduced. Methods: Thirteen black, male subjects between the ages of 19 and 35 years were included in the study. Each subject completed the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Traditionally, physiotherapists do not treat patients with PTB unless they need to assist in the mobilisation of secretions (Goodman & Fuller 2009 ). Hall and de Charmoy ( 2002 ), in their study of young male subjects with PTB, found no reductions in exercise capacity and suggested that the physiotherapist may play more of an educational role in PTB. The study, however, had a small sample size and very particular patient demographics, that is, young male subjects who may already be fitter than the general population by virtue of their gender and age.…”
Section: Discussionmentioning
confidence: 96%
“…Traditionally, physiotherapists do not treat patients with PTB unless they need to assist in the mobilisation of secretions (Goodman & Fuller 2009 ). Hall and de Charmoy ( 2002 ), in their study of young male subjects with PTB, found no reductions in exercise capacity and suggested that the physiotherapist may play more of an educational role in PTB. The study, however, had a small sample size and very particular patient demographics, that is, young male subjects who may already be fitter than the general population by virtue of their gender and age.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the fact that in the present study, there was no exercise training, the results are in accordance with those of Yoshida et al (2006) . Previous study concluded that it seems not necessary to submit patients suffering from pulmonary TB to pulmonary rehabilitation ( Hall and De Charmoy, 2002 ). Nevertheless, in contrary with our study, there was no SpO 2 variation after 2 weeks, may be because of the short duration of the exercise training.…”
Section: Discussionmentioning
confidence: 99%